2007
DOI: 10.1038/sj.onc.1210406
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a PP2A-interacting protein that functions as a negative regulator of phosphatase activity in the ATM/ATR signaling pathway

Abstract: Protein serine/threonine phosphatase 2A (PP2A) activity must be tightly controlled to maintain cell homeostasis. Here, we report the identification of a previously uncharacterized mammalian protein, type 2A-interacting protein (TIP), as a novel regulatory protein of PP2A and the PP2A-like enzymes PP4 and PP6. TIP is a ubiquitously expressed protein and parallels the distribution of the PP2A catalytic subunit. Unlike its role in yeast, TIP does not interact with the mammalian homolog of type 2A-associated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 36 publications
(44 reference statements)
4
90
0
Order By: Relevance
“…Similarly, in mammalian cells, small molecule inhibition of PP2A activity blocks rapamycin-induced dephosphorylation of the mTORC1 substrates 4E-BP1 and S6K1 (18)(19)(20)(21)(22), suggesting that PP2A directly dephosphorylates mTORC1 substrates when mTORC1 activity is inhibited by rapamycin, or that mTORC1 constrains PP2A activity. However, with the latter scenario, it is unclear whether the analogous regulatory paradigm with the Tip41L/α4/PP2A axis in mammals is conserved from yeast (37)(38)(39). Our data are consistent with a regulatory loop involving the MID1/α4/PP2A degradation pathway, where PP2A acts on mTOR itself as opposed to acting on downstream mTORC1 substrates.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, in mammalian cells, small molecule inhibition of PP2A activity blocks rapamycin-induced dephosphorylation of the mTORC1 substrates 4E-BP1 and S6K1 (18)(19)(20)(21)(22), suggesting that PP2A directly dephosphorylates mTORC1 substrates when mTORC1 activity is inhibited by rapamycin, or that mTORC1 constrains PP2A activity. However, with the latter scenario, it is unclear whether the analogous regulatory paradigm with the Tip41L/α4/PP2A axis in mammals is conserved from yeast (37)(38)(39). Our data are consistent with a regulatory loop involving the MID1/α4/PP2A degradation pathway, where PP2A acts on mTOR itself as opposed to acting on downstream mTORC1 substrates.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, in mammalian cells, the inhibitory protein TIP (type-2A-interacting protein) interacts directly with the C subunit in the absence of the A subunit. Its yeast homolog, Tip41p (Tap42p-interacting protein of 41 kDa), however, interacts with and inhibits Tap42p activity [67]. Another non-classical PP2A complex comprises the C subunit, an atypical cyclin, G1 or G2, and a PR61/B 0 subunit [68,69].…”
Section: Important Recent Structural Insightsmentioning
confidence: 99%
“…This suggests that autophosphorylation of ATM is regulated by PP2A and that PP2A may constitutively dephosphorylate ATM in human cells. Recently, McConnell et al (2007) identified a type 2A interacting protein (TIP), which interacts with the catalytic subunit of PP2A and inhibits PP2A phosphatase activity. They also showed that overexpression of TIP causes an increase in phosphorylation of ATM/ATR substrates, and depletion of TIP by siRNA causes a reduction in phosphorylation of ATM substrates.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%